Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Keaktifan Belajar PAK Siswa Kelas IX SMP Negeri 3 Lintongnihuta Tahun Pembelajaran 2023/2024 - Mei Frisda Sihombing; Simion Harianja; Betty A.S. Pakpahan; Johari Manik; Andar Gunawan Pasaribu (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The aim of this research is to determine the positive and significant influence of the Numbered Head Together (NHT) Cooperative learning model on the active learning of PAK class IX students of SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year. The method used in this research uses quantitative descriptive methods. The population is all class IX students of SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year who are Christians totaling 191 people and a sample of 48 people was determined, namely 25% of the total population using random sampling techniques. Data collection used a closed questionnaire with 40 items. The results of data analysis show that there is a positive and significant influence of the Numbered Head Together (NHT) Cooperative learning model on the active learning of PAK class IX students at SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year. Based on the positive relationship test, the value obtained is rxy = 0.606 > rtable(=0.05, n=48) = 0.284, thus it is known that there is a positive relationship between variable ttable(=0.05,dk=n-2=46)= 2.021, thus there is a significant relationship between variable X and variable Y. Regression coefficient of determination test (r2) = 36.8%. Influence test: Regression equation test, the regression equation Y ̂="2.17"+0.63 63. Thus Ha is accepted and H0 is rejected.